Sex-ratios of Swedish Mallard during the non-breeding season - Nilsson, Leif (Wildfowl, 1976)
Sex ratios of non-breeding Mallard Anas platyrhynchos in south Sweden were compared with published information from other parts of Europe. Males outnumbered females on all occasions, this dominance being especially marked early in the season. In winter, this preponderance of males was more marked in northern, continental, and exposed coastal areas. Habitat variation was slight, the preponderance of males being slightly lower on natural lakes as compared with urban waters and coastal waters.